EXPRESSION OF REALITY IN CHILDREN'S TEXTS (Scientific journal of the Fergana State University, 2024)
In this article, national realities, that is, the names of subjects, events and objects characteristic of the life, lifestyle, culture, socio-historical development of a particular people, which are not very familiar or foreign to other peoples, and have a clear alternative in their languages It was analyzed on the example of children's rituals and children's games that the words or phrases expressing the national color are one of the types of lexicon without alternatives. It is proved in the examples that in our nation, the religious views related to the birth of a child and child's upbringing, the ritual and the poetic texts performed in it, the applause as a genre has its historical roots and creates realities with the circumstances of transformation.